Reinforcing mechanisms of natural fibers in green composites: Role of fibers morphology in a PLA/hemp model system. (18th August 2019) - Mazzanti, V.; Pariante, R.; Bonanno, A.; Ruiz de Ballesteros, O.; Mollica, F.; Filippone, G.
Abstract: Green composites, i.e. biodegradable polymers reinforced with natural fibers, are attracting interest as potential substitutes for conventional composites based on petroleum derived plastics. The role of the inherently complex morphology of natural fibers in their reinforcing mechanisms is not completely understood and this is the topic of the present study. The selected system was poly-(lactic acid) filled with 3 and 6 wt% of short hemp fibers. Such a low fiber amount was chosen to help visualization of the fiber – matrix interface at the scanning electron microscope. Remarkable differences in the mechanical behavior were found between composites containing fibers that were alkali treated with respect to untreated fiber filled materials, but unexpectedly it was found that the quality of the fiber – matrix interface was only marginally influenced by the alkaline treatment. Interface properties were thus not exhaustive in explaining the observed differences. On the other hand, the main difference between treated and untreated fibers was the presence, in the untreated fibers population, of a volumetrically relevant sub-population of thick fiber bundles. It was further argued that this fraction did not carry the loads transferred across the fiber-matrix interface uniformly in its cross section, thus determining a reduction in the effective fiber volume fraction. In contrast, the combined action of alkalization and the mechanical stresses during melt mixing resulted in a narrow distribution of isolated elementary fibers, which were more effective in providing higher mechanical properties, in agreement with theoretical predictions. The key message for the scientific community interested in maximizing the mechanical performances of green composites is that, besides trying to improve the quality of the fiber-matrix interface, one should also aim at minimizing the amount of fiber bundles.